COMPARISON OF VAGINAL AND ABDOMINAL HYSTERECTOMY: PERI- AND POST-OPERATIVE OUTCOME - Dawood, Nasira Sabiha; Mahmood, Rabia; Haseeb, Naila (Journal of Ayub Medical College Abbottabad, 2009)
Background: Abdominal and vaginal hysterectomies are the two predominant operative modalities for various uterine conditions; however the indications for selecting a particular procedure in any setting may not be optimally defined. This study was undertaken to evaluate the appropriate route of hysterectomy (abdominal or vaginal) in a hospital population for women with benign disease by comparing peri-operative and post-operative complications. Methodology: This quasi-experimental study was undertaken at the Department of Obstetrics and Gynaecology, Fauji Foundation Hospital/Foundation University Medical College, Rawalpindi from January to December 2007. Eighty subjects were equally divided into vaginal and abdominal hysterectomy groups by convenience (non-probability) sampling. The primary outcome measures were operative time, primary haemorrhage, wound infection, post-operative analgesia, febrile morbidity, hospital stay and secondary haemorrhage; secondary outcome measure were estimated cost, re-admission and reopening. Results: There were no differences in the patients' mean age, parity, body mass index, and preoperative haemoglobin levels between groups. Vaginal hysterectomy was associated with less febrile morbidity, wound infection operative time, economic cost, bleeding requiring transfusion and re-admission than abdominal hysterectomy. Main indication for women having abdominal operation was leiomyomas, whereas more women having uterovaginal prolapse had vaginal hysterectomy. Conclusion: Patients requiring a hysterectomy for benign lesions having a moderate-sized uterus can be offered vaginal route for surgery. Keywords: Hysterectomy, Abdominal hysterectomy, vaginal hysterectomy, indications, postoperative outcome, post-operative complications